2017
DOI: 10.1007/s00701-017-3334-6
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of outcomes following traumatic brain injury—relationship between functional impairment and health-related quality of life

Abstract: BackgroundThe outcome following traumatic brain injury (TBI) is heterogeneous and poorly defined and physical disability scales like the extended Glasgow Outcome Score (GOSE) while providing valuation information in terms of broad categorisation of outcome are unlikely to capture the full spectrum of deficits. Quality of life questionnaires such as SF-36 are emerging as potential tools to help characterise factors important to patients’ recovery. This study assessed the association between physical disability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 40 publications
(37 reference statements)
2
6
1
4
Order By: Relevance
“…Based on a close examination of the relative proportions of patients who underwent decompressive craniectomy and/or received ICP monitoring and/or a shunt device, 58 to 70% were either primarily or secondarily severe brain injured, thus our cohort is comparable to the QOLIBRI validation cohort [38]. Other factors regarding our cohort, including TBI etiology and sex distribution, were consistent with the literature [23,28,39].…”
Section: A Representative Tbi Cohortsupporting
confidence: 75%
“…Based on a close examination of the relative proportions of patients who underwent decompressive craniectomy and/or received ICP monitoring and/or a shunt device, 58 to 70% were either primarily or secondarily severe brain injured, thus our cohort is comparable to the QOLIBRI validation cohort [38]. Other factors regarding our cohort, including TBI etiology and sex distribution, were consistent with the literature [23,28,39].…”
Section: A Representative Tbi Cohortsupporting
confidence: 75%
“…Results indicate that neurocognitive functioning is impacted by CS and may affect HRQL. In other diseases, such as traumatic brain injury and multiples sclerosis, there is evidence of a moderate correlation between physical function and HRQoL, as the two dimensions are linked but not redundant [48, 49]. A PRO measure to assess neurocognitive functioning can be confounded by the degree of neurocognitive impairment the patient has experienced.…”
Section: Discussionmentioning
confidence: 99%
“…To form a more comprehensive picture of the challenges that families face after TBI, it is important to include the perspectives of both the patients and their family members [ 20 ]. Previous research has demonstrated that personal, familial, and social characteristics and injury severity affect HRQL, disease burden, and family adjustment after TBI [ 21 , 22 , 23 ]. However, there is a paucity of knowledge on mental health and family functioning related to the consequences of TBI, which include the impact on these outcomes for members within the same family system.…”
Section: Introductionmentioning
confidence: 99%